2010
DOI: 10.1016/j.aip.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Theater for, by and with fibromyalgia patients – Evaluation of emotional expression using video interpretation

Abstract: The healing function of theater is reflected in all human cultures. Today, therapists and scientists work with psychodrama and drama therapy, often describing theater as the art form closest to life itself. In a unique cooperation between professional actors and a dance movement therapist/pain researcher, patients with fibromyalgia have first been trained in body-and voice expression and thereafter acted out a drama onstage together with professional actors. A video interpretation technique was used to help pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…These studies typically assess measures of well‐being and mood change, depression scores or other psychological outcomes pre‐ and post‐intervention. Specifically, DMT has been used to improve well‐being in patients diagnosed with breast cancer (Goldov, 2011; Sandel et al, 2005), dementia (Ho et al, 2018; Hokkanen et al, 2008), fibromyalgia (Bojner Horwitz, Kowalski, & Anderberg, 2010; Bojner Horwitz, Kowalski, Theorell, & Anderberg, 2006), brain trauma (Berrol, 2009), hypertension (Aweto, Owoeye, Akinbo, & Onabajo, 2012), Parkinson's disease (Abraham, Hart, Andrade, & Hackney, 2018; Earhart, 2009; Hackney, Kantorovich, Levin, & Earhart, 2007; Kiepe, Stöckigt, & Keil, 2012), cystic fibrosis (Goodill, 2005) and Alzheimer's disease (Dayanim, 2009). DMT has been shown to improve a range of mental health and well‐being measures including mood, vitality, self‐efficacy/coping, body image and anxiety (Goodill, 2006 in Koch, Morlinghaus, & Fuchs, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These studies typically assess measures of well‐being and mood change, depression scores or other psychological outcomes pre‐ and post‐intervention. Specifically, DMT has been used to improve well‐being in patients diagnosed with breast cancer (Goldov, 2011; Sandel et al, 2005), dementia (Ho et al, 2018; Hokkanen et al, 2008), fibromyalgia (Bojner Horwitz, Kowalski, & Anderberg, 2010; Bojner Horwitz, Kowalski, Theorell, & Anderberg, 2006), brain trauma (Berrol, 2009), hypertension (Aweto, Owoeye, Akinbo, & Onabajo, 2012), Parkinson's disease (Abraham, Hart, Andrade, & Hackney, 2018; Earhart, 2009; Hackney, Kantorovich, Levin, & Earhart, 2007; Kiepe, Stöckigt, & Keil, 2012), cystic fibrosis (Goodill, 2005) and Alzheimer's disease (Dayanim, 2009). DMT has been shown to improve a range of mental health and well‐being measures including mood, vitality, self‐efficacy/coping, body image and anxiety (Goodill, 2006 in Koch, Morlinghaus, & Fuchs, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…to write for 4 days at home about neutral time management Written expression therapy methods: 4 days of writing compared to control, with 1- and 3-month follow-up Group differences in immediate mood effects and changes in health (pain) from baseline to 1-month and 3-month follow-ups were examined Methods of measurement: pain, fatigue, psychological wellbeing Linguistic Inquiry and Word Count (LIWC) software; Positive and Negative Affect Schedule-Expanded Version (PANAS-X); Fibromyalgia Impact Questionnaire; FIQ; pain subscale from the Arthritis Impact Measurement Scale-2 (AIMS2); Fatigue Severity Scale (FSS); 4-item scale of sleep quality Immediate increase in negative mood, did not attenuate across 4 day. Fewer health benefits after the long term; nonsignificant reduction in pain Integrate written disclosure with other techniques in holistic pain management treatment is necessary Cost-effectiveness: n.d. Written expression Active Graham et al (2008) [ 47 ] Funding: American Psychological Association, Stony Brook University, NIH Grant R01HD39753 Randomized control trial Randomization: randomly assigned into two group Study registration: none To prove the effect of expressing anger for chronic pain sufferers Population: adult Health problem: chronic pain Number of participants: N = 102; 22–70 years old (M = 46.3, SD = 7.5) 1st group n = 51 to express anger constructively 2nd group n = 51 to write about goals non-emotionally in a letter-writing task Written expression therapy methods: two 20-min writing sessions, 2.5 weeks apart; utilizing the anger expression component versus non-emotional writing, with 4- and 9-week follow-up Methods of measurement: anger, depressed mood, pain severity, control over pain Pain Severity subscale of the West Haven-Yale Multidimensional Pain Inventory (MPI); Control subscale of the Survey of Pain Attitudes (SOPA); Center for Epidemiological Studies Depression Scale (CES-D); Revised Life Orientation Test; Anger Behavior-Verbal scale; State-Trait Anger Expression Inventory Over a 9-week period, participants in 1st group (anger-expression group) experienced greater improvement in control over pain and depressed mood, and greater improvement in pain severity than the control group Include more session and include in holistic approach of pain management Cost-effectiveness: n.d. Drama–dance/movement therapy (DDMT) Passive Horwitz et al (2010) [ 42 ] Funding: none Experimental study Randomization: none Study registration: none Population: 7 adults Health problem: fibromyalgia Number of participants: n = 7 (1...…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 studies found, eight dealt with visual art therapy [ 4 , 20 , 31 , 33 35 , 50 , 51 ], one with music therapy [ 40 ], four with dance/movement therapy [ 42 , 43 , 49 , 60 ], and three with written expression [ 45 47 ]. The representation of individual types of arts therapy was not uniform; the least in the field of music was one and the most in the field of visual art therapy were eight.…”
Section: Resultsmentioning
confidence: 99%
“…In knowing that ethnodrama performances are not generalized experiences portrayed on stage, but rather particular lived experiences portrayed to an audience (Saldaña, 2005), Amicus should be accompanied by break-out sessions or group discussions after the performance to enhance the translation from art into practice (Sandelowski et al, 2006) as seen in other health-related research and performances (Boydell et al, 2016; Horwitz et al, 2010). Thus, organizers should tailor their discussion and materials to the needs of that community.…”
Section: Recommendations For the Performance Of Amicusmentioning
confidence: 99%